O roli i pozycji badacza w badaniach rzeczywistości szkoły specjalnej i integracyjnej - Gajdzica, Zenon (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2013)
What the study presents is an authorial concept of one of the possible typologies of the research into special education (in special, integrated and mainstream school). The starting point of this typology is the role and rank of the researcher (actor – observer) applied in various research concepts. In the further part, this is juxtaposed with the studies based on direct and indirect data collection. The essence of the text is an analysis of trendy and infrequent types of studies in the indicated field. This analysis incidentally refers to the correctness of the conducted explorations. The study is completed with final conclusions, which comprise a short list of the neglected issues in the field of special education.